Children's Literature in Critical Contexts of Displacement: Exploring the Value of Hope - Julie E. McAdam; Susanne Abou Ghaida; Evelyn Arizpe; Lavinia Hirsu; Yasmine Motawy (MDPI AG, 2020)
The article builds upon work carried out through a Children's Literature in Critical Contexts of Displacement (CLCCD) network funded by the Arts and Humanities Research Council-Global Challenges Research Fund. The network brought together academics as well as government and non-governmental organisations with expertise in children's literature, migration, and education who were actively working in Egypt and Mexico. They collaboratively designed workshops that examined the use of children's literature as a cultural tool for post-crisis interventions that could contribute to creating a safe space for children and their families to reimagine and restore their self and group identities. This article begins by unravelling the concept of hope, arguing for a critical understanding of hope for transformative use within contexts of flux. Using a critical content analysis approach, five picturebooks used by Egyptian and Mexican mediators were analysed in order to develop an understanding of how critical hope developed within the texts. The emerging themes have been expanded into a set of guiding questions that will enable mediators and educators to use children's literature in contexts of displacement or precarity.